A cross-national comparison of violence among young men in China and the UK: psychiatric and cultural explanations - Coid, Jeremy (Soc Psychiatry Psychiatr Epidemiol, 2017)
PURPOSE: Public health psychiatry has a key role in violence prevention. Cross-national comparisons of violence and associated psychiatric morbidity can indicate targets for preventive interventions. METHOD: Data on young adult men in households, 18–34 years, were drawn from the Second Men’s Modern Lifestyles survey in Great Britain (n = 2046) and from a corresponding survey in Chengdu, China (n = 4132), using a translated questionnaire. Binary logistic regression models were carried out to estimate the cross-national differences for different types of violence and to identify explanatory variables. RESULTS: Chinese men were less likely to report violence in the past 5 years (AOR 0.59, 95% CI 0.48–0.72, P < 0.001). All levels of violence were lower among Chinese men except intimate partner violence (AOR 2.43, 95% CI 1.65–3.59, P < 0.001) and a higher proportion of Chinese men were only violent towards their partners (AOR 7.90, 95% CI 3.27–19.07, P < 0.001). CONCLUSIONS: Cross-national differences were explained by British men’s reports of early violence persisting into adulthood, confidence in fighting ability, perception that violence is acceptable behaviour, and experience of violent victimization. More British men screened positive for antisocial personality disorder and substance misuse. Attitudes which condone violence and a serious problem of alcohol-related, male-on-male violence are key targets for preventive interventions among British men. The higher prevalence of life course-persistent antisocial behaviour among British men is of concern and requires further investigation. Higher prevalence of intimate partner violence among Chinese men reflects patriarchal approaches to conflict resolution and confirms an important public health problem in China which requires further cross-national investigation.